World Literature in and for Pandemic Times - Damrosch, David, (Literature and Cultural Studies E-Books Online, Collection 2026., 2026)
Exploring the emotional and political ramifications of pandemics worldwide, the contributors to this collection treat material from wisdom literature and philosophy to historical fiction, poetry, graphic novels, and hypertexts, and they discuss works from Argentina, Australia, Canada, China, Cuba, Ecuador, Egypt, England, France, Germany, Guatemala, India, Italy, Mexico, Portugal, Turkey, and the United States. Even now that the Covid-19 pandemic has been brought under some degree of control, the lessons-and the wounds-of this traumatic time will long be with us. As we prepare for the inevitable appearance of the next pandemic, world literature can help us create solidarity and collective connection in the years ahead.